The Use of Two-Way Conversation Strategy on Students’ Speaking Performance - Juliana; Risa Anggraini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This investigation investigates the impact of a two-way conversation strategy on the speaking performance of tenth-grade students at SMA Wirakarya Mandiri Medan. A genuine experimental design was implemented, with 160 students being divided into two groups: an experimental group that implemented the two-way conversation strategy and a control group that implemented conventional teaching methods. The students' speaking performance was assessed in areas such as fluency, pronunciation, and vocabulary through pre- and post-tests. The experimental group exhibited substantial improvement in the results, with scores increasing from a pre-test range of 60–79 to a post-test range of 75–89. Conversely, the control group demonstrated negligible improvement, with post-test scores ranging from 61 to 77. The study's results indicate that the two-way conversation strategy substantially improves students' speaking performance in comparison to conventional methods. The results of this study indicate that the two-way conversation strategy can be a successful method for enhancing English-speaking performance in classroom environments, providing educators with a better understanding of more interactive and engaging teaching methods.